The Effect of Green Motivation and Green Creativity on Performance: The Mediating Role of Green Innovation - Suprapti, Anastasia Riani; Aini, Intan Novela Qurrotul; Harsono, Mugi; Sedera, Rakotoarisoa Maminiaina Heritiana (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: The study's purpose is to examine the mediating role of green innovation on the influence of crucial green motivation and green creativity on product development performance in Traditional Herbal Medicine SMEs in Sukoharjo, Indonesia. In the context of increasing environmental awareness, green innovation is the key to creating friendly products that can maintain and improve the competitiveness of the SME industry.Methodology: This study obtained data by questionnaires distributed to 205 Traditional Herbal Medicine SMEs owners with continuous sampling techniques. Using Smart PLS 3.2.9 software, this study used the partial least square method and the bootstrapping test to conduct hypothesis testing of the variables in the research.Finding: The study's findings demonstrate that green drive and green creativity positively influence green innovation. Furthermore, green innovation has been demonstrated to modulate the impact of green motivation on product development performance. The study's results demonstrate that the green creativity variable does not significantly impact green motivation and green innovation is not established as a mediator between green creativity and product development performance.Conclusion: The study's findings indicate that organizations capable of integrating green innovation into their business strategy will be better equipped to confront future difficulties and contribute to environmental sustainability.